FUNGSI DAN MAKNA PATUNG TEHEMBOWO DI SITUS HILIGOWE, KABUPATEN NIAS, BAGI MASYARAKAT PENDUKUNGNYA - Ketut Wiradnyana (Berkala Arkeologi Sangkhakala, 2006)
Tehembowo is one of the Megalithic statue which be located inHili Gowe Sites. This statue indicated that there was a fondrako,that is a ceremony of the legalization of custom regulation inSisarahili and around the village. Besides that, the statue has adeep meaning and function related to Nias community social life.